Analisis Butir Soal Ulangan Harian Semester Gasal Menggunakan Google Formulir di SMA Ipiems Surabaya - Naufal Fikri Firmansyah; Rufi’i (Syntax Corporation Indonesia, 2023)
This research aims to (1) determine the quality of the daily test items for the even semester of class The sample for this research was students of class X Merdeka 5 at SMA Ipiems Surabaya with 33 students as respondents. This research instrument includes multiple choice questions and answer keys resulting from students' work, then tabulated analysis, validity, reliability, difficulty of questions, and differentiability of question items using the help of Microsoft Excel software. The results of this research show that of the 20 multiple choice questions, 21 students completed the multiple choice questions with a reliability value of r11 0.611, rtable level 1% 0.424, 1% reliable category, and the item difficulty index obtained was a value of 11 items in the medium category, 9 questions in the easy category, and 0 questions in the difficult category.